Etika dan Kode Etik Pustakawan sebagai Profesionalisme di Perpustakaan - Yusniah Yusniah; Eka Andria Yani (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2023)
This study aims to explain how librarian professional ethics work as professionalism for the librarian profession. This research method uses the literature review method, from various journals and other written sources that support the discussion of article content. The result of this discussion is that the librarian code of ethics must be understood by members of the profession so that members of the librarian profession carry out their duties for users, colleagues, members of other professions, and the public. As stated in the Librarian Code of Ethics, librarian members are expected to be able to apply the rules written in the Librarian Code of Ethics and practice them in carrying out their duties. Keywords: Ethics, code of ethics, librarians